Aiming at one’s best self – Wellness as a new means for self-branding - Ulla Hakala; Miia Grénman; Barbara Mueller (Germany, 2022)
Much like self-branding, the concept of wellness has emerged in discussions reflecting current self-care culture. This paper examines wellness as a potential means of self-branding. The following research questions are addressed:  1) Through which activities and practices do consumers pursue and consume wellness, and why? 2) How can these practices be used as a means of branding oneself? To address these questions, a series of focus group interviews were conducted in California and Finland – 6 in each.  Transcripts of the sessions were analyzed employing a qualitative content analysis approach.  Several themes emerged from the analysis.  Participants noted that being fit was associated not only with one’s physical condition, but also with emotional and mental health.  Additionally, a shift toward immaterial means of taking care of oneself was noted.  Wellness has become a powerful means of transforming oneself, and it would bode well for corporations to understand the emergence of this new mindset in the self-care culture.
48th EMAC Annual conference: Proceedings